2021
DOI: 10.1161/circ.144.suppl_1.10135
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 10135: Cardiotoxicity and Mortality in Chimeric Antigen Receptor T Cell Therapy Recipients

Abstract: Introduction: Chimeric antigen receptor T cell (CAR-T) therapy harnesses a patient’s own immune system to target cancer. Cardiotoxicity occurs in up to 25% of patients treated with CAR-T. There are limited data characterizing the association between the development of cardiotoxicity after CAR-T and mortality among patients following CAR T cell therapy. Hypothesis: We hypothesized that cardiotoxicity following CAR-T treatment would be associated with a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The incidence of cardiac events in patients receiving CAR-T cells varies between studies but is generally between 10 and 20% and occurs mainly in CRS grade ≥2 with elevated cardiac troponin and interleukin-6. 67 68 69 70 71 72 73 The most frequently observed CV events are profound hypotension requiring vasopressor support, arrhythmias including AF and ventricular tachycardias, as well as left ventricular dysfunction, decompensated HF, and CV death. 67 68 69 70 71 72 73…”
Section: Cardiotoxicity Of Targeted Therapies In Hematologymentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of cardiac events in patients receiving CAR-T cells varies between studies but is generally between 10 and 20% and occurs mainly in CRS grade ≥2 with elevated cardiac troponin and interleukin-6. 67 68 69 70 71 72 73 The most frequently observed CV events are profound hypotension requiring vasopressor support, arrhythmias including AF and ventricular tachycardias, as well as left ventricular dysfunction, decompensated HF, and CV death. 67 68 69 70 71 72 73…”
Section: Cardiotoxicity Of Targeted Therapies In Hematologymentioning
confidence: 99%
“…67 68 69 70 71 72 73 The most frequently observed CV events are profound hypotension requiring vasopressor support, arrhythmias including AF and ventricular tachycardias, as well as left ventricular dysfunction, decompensated HF, and CV death. 67 68 69 70 71 72 73…”
Section: Cardiotoxicity Of Targeted Therapies In Hematologymentioning
confidence: 99%
“…[6][7][8] Recent studies have shown that cardiovascular (CV) events after CAR-T can occur in up to one in four-five patients, including cardiomyopathy (10%), clinical heart failure (6%), and myocardial infarction (MI) (5%). [9][10][11][12][13][14] However, it is unknown whether the occurrence of a CV event impacts mortality in patients undergoing CAR-T. Understanding the association between CV events and mortality is important to further advance CV monitoring guidelines in CAR-T recipients. 15 Similarly, prevention and early treatment of cardiotoxicity may further improve survival outcomes in this population.…”
Section: Introductionmentioning
confidence: 99%